Size limitations and wear behavior of TiB2 coated micro end mills (Ø < 50 µm) when machining cp-titanium - Bohley, Martin; Kieren-Ehses, Sonja; Heberger, Lukas; Kirsch, Benjamin; Aurich, Jan C. (Procedia CIRP, 2018)
Today, medical, biochemical or personal devices are often micro structured to enhance their functionality. Examples for these functionalized products are micro reactors, telecommunication systems or anti-counterfeiting devices. For the mass production of these micro structures, processes like LiGA (lithography, electroplating, and molding) or laser are well established, but the economic high quality manufacturing of protoypes or small batches is still challenging. Among others, micro milling is one of the most promising processes to fulfill those demands. However, this process is limited by the wear behavior of the tools. Due to size effects and the consequential high amount of abrasive wear of the micro end mills, structure sizes as well as the machining speed and accuracy are limited. The cutting edges of the micro end mills are subject to a high amount of abrasive wear. This is due to the high rβ/h-ratio (cutting edge radius to chip thickness ratio), resulting in a high amount of ploughing. This could be compensated by using sharper tools (lower rβ). However, the cutting edge radius is typically in the dimension of the grain size of the cemented carbide used as tool blanks and can therefore currently not be further reduced. As an alternative to lower the wear, micro end mills can be coated. In this research article, micro end mills with a diameter smaller than 50 µm were coated with a Titanium Di-Boride coating (TiB2). The layer hardness is aprox. 4,000 HV and the B2 in the coating reduces the friction while machining. The resulting wear behavior of the coated micro end mills is examined and the minimal tool diameter, where coating and machining is still possible, is determined. Furthermore, four different tool diameters and the respective ideal TiB2 layer thickness were researched. Thus, the manufacturing of even smaller geometries and parts with better functionality on larger areas with a micro milling process will be possible.